Determination of Metabolizable Energy of Grape Pomace and Raisin Vitis Leaves Using in Vitro Gas Production Technique - Moghaddam, M; Taghizadeh, A; Nobakht, A; Ahmadi, A (ANIMAL PRODUCTION, 2013)
Abstract. This present study was carried out to determine the fermentation characteristics, metabolizable energy (ME), organic matter digestibility (OMD), short chain fatty acids (SCFA), net energy for lactation (NEl) and volatile fatty acids (VFA) of grape pomace (GP) and raisin vitis leaves (RVL) using gas production technique. Two fistulated whether with average BW 45±2 kg were used. The data was analyzed using completely randomized design. The incubation times were 2, 4, 6, 8, 12, 16, 24, 36, 48 and 72 h. The gas production of soluble and insoluble fractions (a+b) were 289.49 and 249.93 mLg-1DM and the rate of gas production prices (c) were 0.015 and 0.024 (%/h) for RVL and GP, respectively. The ME, OMD, NEl and VFA for RVL were obtained 15.74 mjkg-1DM, 96.97%, 0.0505 Mcal/lb and 2.787 mmol, and for GP were achieved 13.63 mjkg-1DM, 87.04%, 0.496 Mcal/lb and 2.484 mmol, respectively, that showed significant differences (P<0.05). The amount of gas production in RVL (126.87 mLg-1DM) that was more than GP (112.10 mLg-1 DM) resulted low ME in GP compared to RVL. It was concluded, that the GP and RVL can be used in ruminants diets formulation.Keywords: metabolizable energy, gas production, grape pomace, vitis leaves Abstrak. Studi ini dilakukan untuk mengetahui karakteristik fermentasi , energi metabolis ( ME ) , kecernaan bahan organik ( OMD ) , asam lemak rantai pendek ( SCFA ) , energi bersih untuk laktasi ( nel ) dan asam lemak volatil ( VFA ) anggur pomace ( GP ) dan daun kismis Vitis ( RVL ) menggunakan teknik produksi gas . Dua berfistula apakah dengan rata-rata 45 ± 2 BW kg digunakan . Data dianalisis dengan menggunakan rancangan acak lengkap . Waktu inkubasi adalah 2 , 4 , 6 , 8 , 12 , 16 , 24 , 36 , 48 dan 72 jam . Produksi gas dari fraksi larut dan tidak larut (a + b ) adalah 289,49 dan 249,93 MLG - 1DM dan tingkat harga produksi gas ( c ) adalah 0,015 dan 0,024 ( % / jam ) untuk RVL dan GP , masing-masing. The ME , OMD , NEL dan VFA untuk RVL diperoleh 15,74 mjkg - 1DM , 96,97 % , 0,0505 Mcal / lb dan 2,787 mmol , dan untuk GP dicapai 13,63 mjkg - 1DM , 87.04 % , 0,496 Mcal / lb dan 2,484 mmol , masing-masing , yang menunjukkan perbedaan yang signifikan (P < 0,05). Jumlah produksi gas di RVL ( 126,87 MLG - 1DM ) yang lebih dari GP ( 112,10 MLG - 1 DM ) menghasilkan ME rendah di GP dibandingkan dengan RVL . Disimpulkan bahwa, GP dan RVL dapat digunakan dalam formulasi diet ruminansia. Kata kunci : inkubasi , produksi gas , anggur pomace , energi metabolis , daun vitis. M Moghaddam et al./Animal Production 15(1):40-46, January 2013